Greenland, landscape of Ice Fjord, Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1931)
Fig 149 - Ice Fiord West of Renbukten. July 30, 1931. (X). (Caption from Boyd, L. A. (1935). The Fiord Region of East Greenland (pp. 111). New York: American Geographical Society.) Ice fiord West of Renbukten Boyd, Louise A. (1935). The Fiord Region of East Greenland. New York: American Geographical Society